Model Pembelajaran Berbasis Proyek pada Mata Kuliah Metode Optimisasi di Program Studi Matematika Fakultas Sains dan Teknologi Universitas Jambi - Niken Rarasati; Syamsyida Rozi; Cut Multahadah (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2022)
This study aims to confirm the effectiveness of implementing the project-based learning (PjBL) model. The results of this study show that applying the PjBL model to the optimization method course has efficacy in terms of positive responses to learning participation according to the outcomes that need to be met at each meeting increase. As many as 100% of student studies show that learning a musical instrument in the form of materials and task plans can stimulate learning and curiosity in students. Additionally, 98% of students said they were delighted with the project assignments, and 2% said they were burdened with their tasks. Ninety percent of students said group work helped them complete a particular project, and 5% of students said they disagreed with their group assignments. In addition to the questionnaire, the effectiveness of implementing the PjBL model can be seen from the written exam results and the given project assignments. These are cumulative to the final value of the optimization technique course. That means 71% of students get an A. 17% A- and 10% B+. The value indicates that the optimization techniques course is very successful, and no student fails while working with the PJBL model